Lake Bacterial Communities in North Patagonian Andes: The Effect of the Nothofagus pumilio Treeline - Bastidas Navarro, Marcela Alejandra (2024)
One of the most noticeable environmental discontinuities in mountains is the transition that exists in vegetation below and above the treeline. In the North Patagonian Andean lakes (between 900 and 1950 m a.s.l.), we analyzed the bacterial community composition of lakes in relation to surrounding vegetation (erected trees, krummholz belt, and bare rocks), dissolved organic carbon (DOC), and total dissolved nutrients (nitrogen, TDN and phosphorus, TDP). We observed a decrease in DOC, TDP, and TDN concentrations with altitude, refecting shifts in the source inputs entering the lakes by runof. Cluster analysis based on bacterial community composition showed a segregation of the lakes below treeline, from those located above. This frst cluster was characterized by the cyanobacteria Cyanobium PCC-6307, while in the krummholz belt and bare rocks, bacterial communities were dominated by Actinobacteria hgcl-clade and Proteobacteria (Sandarakinorhabdus and Rhodovarius), with the presence of pigments such as actinorhodopsin, carotenoids, and bacteriochlorophyll a. The net relatedness index (NRI), which considers the community phylogenetic dispersion, showed that lakes located on bare rocks were structured by environmental fltering, while communities of lakes below treeline were structured by species interactions such as competition. Beta-diversity was higher among lakes below than among lakes located above the treeline. The contribution of species turnover was more important than nestedness. Our study brings light on how bacterial communities may respond to changes in the surrounding vegetation, highlighting the importance of evaluating diferent aspects of community structure to understand metacommunity organization.